Aáeáing taáel, kernel and ear variation in Peruvian highland maize - Abu-Alrub, I.=700 1 Christiansen, J.L.; Madsen, S.; Sevilla, R.; Ortiz, R.
(En, Es, Fr)
ilus., 20 ref.
Keywords: ZEA MAYS; VARIACION GENETICA; TECNICAS ANALITICAS; PERU